Evaluation of the Effect of 2 Flask Investment Materials on Color Stability of 5 Brands of Denture Teeth - Fariborz Vafaee; Sara Tavakolizadeh; Mahdi Kadkhodazadeh; Masoume Khoshhal (Mashhad University of Medical Sciences, 2014)
Introduction: The purpose of this study was to investigate the effect of flask investment materials on the color changes of different brands of resin denture teeth. Methods: Resin denture teeth (560) were divided into 2 groups according to the materials used for flask investment (silicone or gypsum). All the specimens were thermocycled between 4°C and 60°C with 60-s dwell times for 1,000 cycles. Subsequently, the specimens of each group were divided into 4 subgroups based on the immersion media: coffee, tea, cola, and distilled water. Digital images of the teeth were taken before immersion and 30 days after immersion. The color samples were measured using the CIE L*a*b* system, and color differences (∆E) were calculated. The data were evaluated by three ways ANOVA and the Tukey HSD test. Results: There was not a significant difference in ∆E using three-way ANOVA, while the results showed considerable statistical differences with two factor ANOVA interaction. The ∆E values in the silicone group were significantly more than those in the gypsum group (P